Correlation Analysis of Body Weight with Insulin Resistance and Leptin Levels in Farm Workers - Naurah Nazihah Azzalina; Sugiyanta Sugiyanta; Kristianningrum Dian Sofiana (Journal of Agromedicine and Medical Sciences, 2024)
Insulin resistance is a pathological condition resulting from impaired insulin response which causes increased insulin production as a form of compensation from pancreatic beta cells. A stable body weight can prevent insulin resistance and excessive body weight can be a predisposing factor insulin resistance. Individuals with insulin resistance will experience an increase leptin levels 2.3 times more than normal individuals. The aim of this study was to analyze the correlation between body weight and insulin resistance and leptin levels in farm workers. This research method is a cross-sectional analytical observational study conducted from April to September 2023. This research has taken primary data in the form of body weight, fasting blood glucose levels, and insulin and leptin levels from 46 farm worker respondents in Wringin Agung Village, Jombang District, Jember Regency. The results of the Pearson Correlation analysis showed that there was no correlation between body weight and insulin resistance and leptin levels in farm workers. The results of the analysis between body weight and insulin resistance were p = 0.265 with a correlation coefficient of 0.168, which means the degree of correlation is very low. The results of the analysis between body weight and leptin levels were p = 0.870 with a correlation coefficient of 0.025, which means the degree of correlation is very low. The conclusion of this study is that there is no significant correlation between body weight and insulin resistance and leptin levels in farm workers. Keywords: Body weight, insulin resistance, leptin levels